1996
DOI: 10.1111/j.1467-6419.1996.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

PSEUDO‐R2 MEASURES FOR SOME COMMON LIMITED DEPENDENT VARIABLE MODELS

Abstract: A large number of different Pseudo-R2 measures for some common limited dependent variable models are surveyed. Measures include those based solely on the maximized likelihoods with and without the restriction that slope coefficients are zero, those which require further calculations based on parameter estimates of the coefficients and variances and those that are based solely on whether the qualitative predictions of the model are correct or not. The theme of the survey is that while there is no obvious criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
210
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(213 citation statements)
references
References 36 publications
(46 reference statements)
1
210
0
2
Order By: Relevance
“…AIC was used to compare OLS and spatial autoregressive models. Since the OLS models report goodness of fit using R 2 , whereas the spatial autoregressive models use pseudo R 2 , they are not directly comparable (Veall & Zimmermann 1996). The spatial dependence of the two model residuals was also compared using Moran's I scatterplots.…”
Section: Discussionmentioning
confidence: 99%
“…AIC was used to compare OLS and spatial autoregressive models. Since the OLS models report goodness of fit using R 2 , whereas the spatial autoregressive models use pseudo R 2 , they are not directly comparable (Veall & Zimmermann 1996). The spatial dependence of the two model residuals was also compared using Moran's I scatterplots.…”
Section: Discussionmentioning
confidence: 99%
“…Useful surveys are presented by Windmeijer (1995) and Veall and Zimmermann (1996) amongst others. Table 4 reports two such R 2 measures.…”
Section: Ordinal Vs Cardinal Response Scale?mentioning
confidence: 99%
“…This is of the 'explained variation class' of measures in that it mimics the standard R 2 in OLS since it can be interpreted as the ratio of explained sum of squares to the total sum of squares (Veall and Zimmermann, 1996). Simulations suggest that this measure most closely approximates the OLS R 2 for the underlying (unobserved) latent variable model (Hagle and Mitchell, 1992;Windmeijer, 1995) and hence it is an attractive choice.…”
Section: Ordinal Vs Cardinal Response Scale?mentioning
confidence: 99%
“…13 The χ 2 tests of whether the data for males and females could be pooled and a single equation estimated indicated that these samples should be examined separately. Veall and Zimmermann 1996). Absolute value of 't' statistics in parentheses.…”
Section: School Outcomesmentioning
confidence: 99%
“…However, the partial effect is very small, being around one percentage point. Note: The McFadden R 2 is calculated as 1 -(l m /l o ), where l m = the maximised log-likelihood value of the model and l o = the log-likelihood value if the non-intercept coefficients are restricted to zero (see Veall and Zimmermann 1996). Absolute value of 't' statistics in parentheses.…”
Section: Labour Market Outcomesmentioning
confidence: 99%